Limit Analysis of Structures With Destructible Elements Under Impact Loadings - ALIAWDIN, P.; MUZYCHKIN, Y. (Engineering Transactions, 2014)
Limit states and identification of structures with shock- or seismic-protected system under dynamic loadings are discussed. Such structures include both the destructible (elastic-brittle) and indestructible (elastic-plastic) elements. A mathematical model and algorithm for solving shakedown problem of bearing capacity of systems with destructible elements are suggested. Next the propagation of vibrations from impacts of Minsk subway trains into nearby skeleton of 9-storied building is investigated. The experimental data for this building are received. Then the propagation of vibrations is analyzed numerically. Finally, a technique of minimax to evaluate dynamic elastic modules of concrete in the considered structure elements is used.